Does caffeine exert dose-response effects on saliva secretory IgA following prolonged submaximal running? - Dulson, D. K.; Gibson, C. A.; Kilding, A. E.; Lu, J.; Pook, C. (Translational Sports Medicine, 2019)
This study examined the dose-response effects of caffeine on saliva secretory immunoglobulin A (SIgA) responses to prolonged submaximal running. In a double-blind randomized crossover design, 12 endurance-trained male runners (age: 29 ± 3 years, VO2peak 62.7 ± 5.1 mL/kg/min, mean ± SD) ran for 70 minutes at 80% VO2peak 60 minutes after ingesting 0 (PLA), 2 (2CAF), 4 (4CAF), 6 (6CAF) or 8 (8CAF) mg/kg body mass of caffeine. Unstimulated whole saliva samples were obtained pre-supplementation, pre-exercise, mid-exercise, immediately post-exercise, and 1 hour post-exercise. Saliva caffeine concentrations were significantly increased above pre-supplement at all time points following caffeine ingestion in a dose-dependent manner (P < 0.001). Saliva SIgA concentration and secretion rates were unaffected by exercise or caffeine ingestion. Saliva a-amylase activity was higher in 4CAF, 6CAF, and 8CAF when compared to PLA and 2CAF (trial effect, all P < 0.05), but showed no dose-response between trials (trial effect, all P > 0.05). Saliva a-amylase activity was shown to be similar between PLA and 2CAF (P > 0.05). In summary, these findings suggest that regardless of dose, caffeine ingestion 60 minutes prior to prolonged submaximal running has no effect on saliva SIgA responses.